2020
DOI: 10.1016/j.envsci.2020.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impacts on ecosystem services provided by geodiversity in highly urbanised areas: A case study of the Taubaté Basin, Brazil

Abstract: This work presents a method to identify, to evaluate and to quantify the losses of the offer of ecosystem services provided by geodiversity, using as a case study the Taubaté Basin region, a highly urbanized portion of southeastern São Paulo State, Brazil. Our method considers not only the qualitative analysis of the abiotic aspects, but also the historical and cultural context, in which the geodiversity elements are crucial for local economy development. The method is based on: i) Qualitative evaluation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
(46 reference statements)
1
15
0
1
Order By: Relevance
“…The results showed that anthropogenic action is the main factor that alters the availability of local services, with emphasis on the supply of water, soils, and mineral resources, and it potentially influences the quality of life of certain species. Akanksha Balha [34], predicting the impact of urbanization on water resources in the megacity of Delhi, proposed a road map to assess future water availability in various megacities across the globe. Robert Hoyer's [35] assessment of freshwater ecosystem services in the Tualatin and Yamhill basins under climate change and urbanization showed that the estimated relative changes in ES provision under different climate and urbanization scenarios are valuable for land management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that anthropogenic action is the main factor that alters the availability of local services, with emphasis on the supply of water, soils, and mineral resources, and it potentially influences the quality of life of certain species. Akanksha Balha [34], predicting the impact of urbanization on water resources in the megacity of Delhi, proposed a road map to assess future water availability in various megacities across the globe. Robert Hoyer's [35] assessment of freshwater ecosystem services in the Tualatin and Yamhill basins under climate change and urbanization showed that the estimated relative changes in ES provision under different climate and urbanization scenarios are valuable for land management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…These elements describe the form and quality of the area, and they are common throughout the Earth, while other elements of main values (volcanos, caves, weathering mass, and structural elements) are connected to places with conditions that contribute to evolution of these processes. Additionally, soils were not mentioned above, as this element is considered to fall within the sphere of biological activity and will be studied in future research [3,10,[30][31][32][33][34][35]. Notably, soils represent the interface between abiotic and biotic nature and processes, with soil formation and type impacting on the geocultural aspects of societal development, such as evolution of agricultural practices.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of geodiversity is developing as a research field whereby studying abiotic nature can be used an analogue for biodiversity as the living part of the environment. Some researchers seek the best solution to objectively determine the geodiversity of a territory [1][2][3]. Researchers such as Gray, Kozłovskyi, Serrano and others [4][5][6] have established a core definition of geodiversity as the sum of the Earth's history, tectonics, minerals, rocks, sediments, fossils, landforms, geomorphological processes and soils, geological structures, surface water, groundwater, mineral and therapeutic waters, and thermal waters.…”
Section: Introductionmentioning
confidence: 99%
“…These were described in detail by [36]. The geosystem service framework has been applied to the sustainable management of coastal natural resources [41], geodiversity and water resources evaluation [42], environmental impact assessment regarding geodiversity [43], evaluation of geodiversity's cultural services [44], mapping of geosystem services in mountains [45], and tourism studies [46]. Here, we apply the geosystem service concept and framework to examine the spatial reasoning behind MMEDs.…”
Section: Geosystem Services Land Use and Mmedsmentioning
confidence: 99%